2005
DOI: 10.1155/jammc.2005.211
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mercury in an Assortment of Dietary Supplements Using an Inexpensive Combustion Atomic Absorption Spectrometry Technique

Abstract: The concentrations of mercury in forty, commercially available dietary supplements, were determined using a new, inexpensive analysis technique. The method involves thermal decomposition, amalgamation, and detection of mercury by atomic absorption spectrometry with an analysis time of approximately six minutes per sample. The primary cost savings from this approach is that labor-intensive sample digestion is not required prior to analysis, further automating the analytical procedure. As a result, manufacturers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…Levine et al . () attempted to use a combustion atomic absorption spectrometry technique to evaluate the mercury levels in an assortment of dietary supplements including fish oil products. A few other studies reported an analytical method to quantify the heavy metal elements and PCBs in fish oil supplement products (Schantz et al ., ; Gomara et al ., ; Rawn et al ., ; El‐Moselhy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Levine et al . () attempted to use a combustion atomic absorption spectrometry technique to evaluate the mercury levels in an assortment of dietary supplements including fish oil products. A few other studies reported an analytical method to quantify the heavy metal elements and PCBs in fish oil supplement products (Schantz et al ., ; Gomara et al ., ; Rawn et al ., ; El‐Moselhy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Dalman et al (2006) determined the levels of heavy metal elements and trace elements in the fish of the south-eastern Aegean Sea in Turkey using atomic absorption spectrometry. Levine et al (2005) attempted to use a combustion atomic absorption spectrometry technique to evaluate the mercury levels in an assortment of dietary supplements including fish oil products. A few other studies reported an analytical method to quantify the heavy metal elements and PCBs in fish oil supplement products (Schantz et al, 1993;Gomara et al, 2005;Rawn et al, 2006;El-Moselhy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All the chemicals (HCl (Qualigens, 36.5%), HNO 3 (Merck, 65%), and HClO 4 (Rankem, 73%)) used were of analytical grade. All the glassware was soaked with aqua regia (HCl:HNO 3 , 3:1) for 2 h (Levine et al, 2005). The completely dried sample (1 g) was digested in concentrated nitric acid and perchloric acid (3:1) until a clear solution with white fumes was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…monitored 12 and our recent investigations found 15 elements in SJW preparations . Due to the lack of Certified Reference Materials (CRMs) available for SJW, a number of plant‐based CRMs have been reported for accuracy assessments including tomato leaves, peach leaves, spinach leaves, tea leaves, mixed Polish herbs, grass and tobacco …”
Section: Introductionmentioning
confidence: 99%